2006
DOI: 10.1111/j.1469-8986.2006.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention freezes during the attention blink

Abstract: A variant of the rapid serial visual presentation paradigm was used to display sequentially two lateral sequences of stimuli, one to the left and one to the right of fixation, embedding two pairs of target stimuli, T1 and T2. T1 was composed of a pair of alphanumeric characters, and subjects had either to ignore T1 or to encode T1 for a delayed response. T2 was a lateral square of a prespecified color. The square had a small gap in one side, and the task for this stimulus was to report which side had the gap. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
132
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(154 citation statements)
references
References 38 publications
19
132
3
Order By: Relevance
“…These effects are supported by the experimentally observed suppression ('freezing') of the N2pc during the AB period [136,137]. During this period, amplification and ignition in the visual system involving LIP, FEF and the pulvinar are disabled.…”
Section: (Iii) Attentional Selection and Intermediate Buffersupporting
confidence: 61%
See 1 more Smart Citation
“…These effects are supported by the experimentally observed suppression ('freezing') of the N2pc during the AB period [136,137]. During this period, amplification and ignition in the visual system involving LIP, FEF and the pulvinar are disabled.…”
Section: (Iii) Attentional Selection and Intermediate Buffersupporting
confidence: 61%
“…When the GW router for top-down attention is disabled, amplification and ignition processes related to attention cannot take place in the VAW. Indeed, there is evidence of suppression ('freezing') of the N2pc component, related to (spatial) attentional selection in the visual cortex, during the AB [136,137].…”
Section: (Iii) Attentional Selection and Intermediate Buffermentioning
confidence: 99%
“…Furthermore, studies have shown that spatial attention is "frozen" for the first 100 ms of the AB (Du & Abrams, 2010a). Event-related potential studies have also shown that voluntary orienting during the AB is associated with a decreased N2pc magnitude, further showing the susceptibility of these mechanisms to disruption (Dell'Acqua, Sessa, Jolicoeur, & Robitaille, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even a cued switch was accompanied by a cost, probably reflecting the difficulty observers have with disengaging from the location of the still relevant T1 (which obviously did not move with the cue). Work by Dell'Acqua et al (2006) has shown that a relevant T1 induces larger switch costs than does a T1 that can be disregarded. What is more, performance at lag 1 in the cued switch condition appeared to be even worse than that in the uncued switch condition in Experiment 2A.…”
Section: Experiments 2 No Lag 1 Sparing When Attention Switches Locationmentioning
confidence: 99%